2016
DOI: 10.1007/s00125-015-3852-9
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue transcriptomics and epigenomics in low birthweight men and controls: role of high-fat overfeeding

Abstract: Aims/hypothesis Individuals who had a low birthweight (LBW) are at an increased risk of insulin resistance and type 2 diabetes when exposed to high-fat overfeeding (HFO). We studied genome-wide mRNA expression and DNA methylation in subcutaneous adipose tissue (SAT) after 5 days of HFO and after a control diet in 40 young men, of whom 16 had LBW. Methods mRNA expression was analysed using Affymetrix Human Gene 1.0 ST arrays and DNA methylation using Illumina 450K BeadChip arrays. Results We found differential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 48 publications
3
48
1
1
Order By: Relevance
“…The involvement of epigenetic factors in insulin resistance is also supported by the theory of a metabolic memory, linking an impaired intrauterine environment to increased risk for insulin resistance later in life [5].…”
Section: Dnmt Dna (Cytosine-5)-methyltransferase Pbmc Peripheral Bloomentioning
confidence: 94%
“…The involvement of epigenetic factors in insulin resistance is also supported by the theory of a metabolic memory, linking an impaired intrauterine environment to increased risk for insulin resistance later in life [5].…”
Section: Dnmt Dna (Cytosine-5)-methyltransferase Pbmc Peripheral Bloomentioning
confidence: 94%
“…1,[5][6][7] Therefore, epigenetic modifications, either inherited or induced by lifestyles, 8,9 may play a key role in the pathogenesis of the disease. To some extent, the epigenetic mechanisms resulting in aberrant histone modifications, differences in DNA methylation, and dysregulation of microRNAs are the ones that have been related to NAFLD and its transition to more advanced stages.…”
Section: Introductionmentioning
confidence: 99%
“…The literature investigating effects of nutritional challenges on DNA methylation in humans is limited and includes studies addressing effects of high-calorie diets [69]. We have previously found that LBW subjects, when undergoing a high-fat feeding, exhibit less changeability in muscle tissue DNA methylation than matched NBW controls [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, today we experience an increasing understanding of environmental regulation of DNA methylation in adult life, and recent studies have shown that ageing [1–3], exercise [4, 5], and dietary factors [69] can alter site-specific DNA methylation in humans, across different tissues. Epigenetic modifications have further been associated with differential gene expression and altered metabolism in key diabetic tissues, including adipose tissue [4, 1012].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation